Learning outcomes approaches in VET curricula : a comparative analysis of nine European countries - (:unkn) unknown (Publications Office of the European Union, 2010)
"By comparing national curriculum reforms and analysing learning programmes in logistics, this comparative study examines the use of learning outcomes approaches in curriculum development in nine European countries: Germany, Ireland, Spain, France, the Netherlands, Poland, Romania, Slovenia and UK Scotland. Based on an extensive literature review, interviews and surveys conducted with different stakeholders in curriculum policy-making and practice, the findings show how learning outcomes increasingly feature in VET curricula, influencing their development and changing their content and structure. The study reveals differences in the understanding and use of learning outcomes among countries and types of education and training." Often names such as "outputs", "attainments", "products", "aims", "objectives", "capacities", "assessment standards" or "(key) competences" are embedded in different theoretical methods of curriculum development and fulfil different roles and functions within the overall education and training system. (Herausgeber, BIBB-Doku)
Keywords: L 1.3 Curriculumentwicklung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; I 2.1 Deutschland; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; Berufsbildung; Curriculumentwicklung; Kompetenzorientierung; Lernergebnisorientierung; Internationaler Vergleich; Vergleichende Berufsbildungsforschung; Europa; Bundesrepublik Deutschland; Frankreich; Irland; Niederlande; Polen; Rumänien; Slowenien; Spanien; Schottland